1994
DOI: 10.1016/0732-8893(94)90021-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G directed against toxins A and B of Clostridium difficile in the general population and patients with antibiotic-associated diarrhea

Abstract: Serum immunoglobulin G (IgG) class antibodies directed against toxins A and B of Clostridium difficile were studied using an enzyme-linked immunosorbent assay and a serum-neutralizing assay based on the MRC-5 tissue cytotoxicity assay. Of 185 individuals, 46 sera (24%) in the general population demonstrated IgG antibody, 36 (19.4%) against toxin A and 15 (8.1%) against toxin B. Antibody titer in the general population did not correlate with serum-neutralizing activity. Antibody prevalence fell with age (P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 8 publications
3
23
0
1
Order By: Relevance
“…Toxinreactive IgG and IgA can be detected in the intestine and serum and have the potential to block toxin binding to epithelial receptors and promote toxin clearance from the intestine (71). The presence of antibodies that are reactive to C. difficile TcdA has been positively correlated with asymptomatic carriage of C. difficile (32), although there are conflicting reports regarding whether naturally occurring antitoxin antibodies and intravenous immunoglobulin therapy (IVIG) affect the disease course (32,69,70,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83). Questions thus remain as to the extent to which antibody levels may confer protection against CDI.…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
See 1 more Smart Citation
“…Toxinreactive IgG and IgA can be detected in the intestine and serum and have the potential to block toxin binding to epithelial receptors and promote toxin clearance from the intestine (71). The presence of antibodies that are reactive to C. difficile TcdA has been positively correlated with asymptomatic carriage of C. difficile (32), although there are conflicting reports regarding whether naturally occurring antitoxin antibodies and intravenous immunoglobulin therapy (IVIG) affect the disease course (32,69,70,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83). Questions thus remain as to the extent to which antibody levels may confer protection against CDI.…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
“…Natural anti-C. difficile TcdA and TcdB antibodies in the general population have been proposed to be protective factors against disease development (69,70). Toxinreactive IgG and IgA can be detected in the intestine and serum and have the potential to block toxin binding to epithelial receptors and promote toxin clearance from the intestine (71).…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
“…It has been shown that many such donors express high anti-toxin A and anti-toxin B antibody serum titers. 38,39 In addition, high levels of anti-toxin A and anti-toxin B antibodies were present in the IVIG preparations and the recipients after infusion. [15][16][17]22 Although constituting only a small fraction of the total IVIG administered, these antitoxin antibodies are believed to neutralize toxin A and B and help the host recover from the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Johnson et al measured anti-TcdA IgA and IgG in CDI patients and controls and found higher titers in convalescent CDI cases than healthy controls, but no correlation with clinical outcome, even when the ability of the antibodies to neutralize cytotoxicity was measured [24]. Similarly, Bacon and Fekety found antiTcdA/B IgG in 24% of healthy control blood samples, although titer by ELISA did not correlate with neutralizing activity, which was measured at up to 1:50 serum dilution [25]. This stands in contrast to an earlier study that found anti-TcdA or TcdB in over 64% of healthy blood donors, with high titres correlating with neutralization [26].…”
Section: Anti-c Difficile Antibodies In Primary Versus Recurring CDImentioning
confidence: 99%